Synopsis of Most Relevant Articles on Cardiac Arrhythmias: Sinopse de Artigos Mais Relevantes em Arritmias Cardíacas - Papelbaum, Bruno P (JOURNAL OF CARDIAC ARRHYTHMIAS, 2019)
Sinopse of the most relevant papers published in J Am Coll Cardiol EP, Heart Rhythm, Arrhythm Electrophysiol Rev. e JACC: Clinical Electrophysiology.